Identitas Kaum Muda dalam Live Performance Musik Punk di Bali - Sintawati, Tjok Istri; Sutopo, Oki Rahadianto (Jurnal Sosiologi Andalas, 2026)
This article explores how youth in Bali construct and negotiate subcultural identities through their experiences as concert-goers at punk live performances. Drawing on post-subcultural perspectives and theories of late modernity particularly Maffesoli’s concept of neo-tribes and Giddens’ notion of reflexive individualization, the study positions punk live performances as affective arenas where identity work unfolds beyond rigid scene-based participation. The study adopts a multi-sited ethnographic approach, combining participant observation at two punk live performance events in Bali, in-depth interviews with four young male concert-goers, and documentation through fieldnotes, photographs, and videos. Data were thematically coded and analyzed using frameworks from youth culture studies, neo-tribal sociality, and reflexive identity formation. The findings demonstrate that punk live performances generate distinctive affective dimensions, including collective energy, embodied expressivity, and a sense of belonging. Practices such as moshing, shared gestures, and symbolic dress enable temporary social bonds among concert-goers, including those not actively involved in local punk scenes. These affective encounters facilitate symbolic exchange and experiential intensity that differentiate punk live performances from other cultural spaces. The discussion argues that such temporary yet intense experiences serve as resources for reflexive self-narration and the projection of subcultural identities in late modernity. Punk identities in contemporary Bali are increasingly shaped through fluid, consumption-based participation rather than stable subcultural membership.